THE EFFECT OF LAND CHANGE ON ENVIRONMENTAL CONDITIONS IN THE PERI-URBAN AREA OF SAWAHAN VILLAGE AND THE RELATION TO SUSTAINABLE CITIES AND SETTLEMENTS - Wahyu Gilang Hermawan; Ulfi Hanum (Nusantara Hasana Journal, 2023)
Sawahan Village is one of the villages in Boyolali Regency which acts as a bridge between the surrounding villages and the city of Surakarta which has undergone land changes for development development. Even though Sawahan Village is an urban area that should have a higher green space area than the gray space area. The purpose of this study was to determine the factors causing land changes and the effect of changes in the availability of green space for agricultural land as a result of development developments on environmental conditions in the peri-urban area of Sawahan Village, Ngemplak District, Boyolali Regency, and to determine the suitability of the conditions of Sawahan Village regarding the destination of the 11 SDGs. This study uses interviews, observation and triangulation with purposive sampling techniques so that the data used can be collected in the form of words and actions, written data sources, documentation and statistical data. Based on research results, in 2000 the condition of green space was wider than the gray space, while in 2010 and 2020 the condition of the gray space was wider than the green space. Changes in the availability of green space for agricultural land will affect the environmental conditions in Sawahan Village. From the aspect of the physical environment, land change has an impact on damage to land ecosystems and will have a sustainable impact on the occurrence of natural disasters such as floods and landslides. Land changes also affect the quality of groundwater, where 30% of the people of Sawahan Village are no longer using wells as their main source of clean water. The groundwater discharge in the well has also decreased, from 75% of respondents who own wells, as many as 50% said that the surface or well water debit has decreased. Apart from that, air quality will also be affected, where 30% of the people of Sawahan Village admit that there is a significant difference in air quality after the construction of the toll road. From the aspect of the social environment, 70% said that the environment where they live is still relatively good and the need for community facilities and infrastructure is more fulfilled. Meanwhile, from the economic aspect, it has an impact on changes in livelihoods, where 60% have community livelihoods in the non-agricultural sector which are supported by an increase in per capita income of the population. The effect of land change is of course also related to cities and sustainable settlements. Based on the goals of the 11th SDGs, Sawahan Village is classified as still reaching the Significant Challenges Remain level. This is because the targets achieved have been significant but there are still targets that have not been achieved. Therefore, development in Sawahan Village must prioritize and maintain aspects of sustainable development.